Impedance changes in chronically implanted and stimulated cochlear implant electrodes. (July 2014) - Newbold, Carrie; Mergen, Silvana; Richardson, Rachael; Seligman, Peter; Millard, Rodney; Cowan, Robert; Shepherd, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Electrode impedance increases following implantation and undergoes transitory reduction with onset of electrical stimulation. The studies in this paper measured the changes in access resistance and polarization impedance in vivo before and following electrical stimulation, and recorded the time course of these changes. Design Impedance measures recorded in (a) four cats following 6 months of cochlear implant use, and (b) three cochlear implant recipients with 1.5–5 years cochlear implant experience. Results Both the experimental and clinical data exhibited a reduction in electrode impedance, 20 and 5% respectively, within 15–30 minutes of stimulation onset. The majority of these changes occurred through reduction in polarization impedance. Cessation of stimulation was followed by an equivalent rise in impedance measures within 6–12 hours. Conclusions Stimulus-induced reductions in impedance exhibit a rapid onset and are evident in both chronic in vivo models tested, even several years after implantation. Given the impedance changes were dominated by the polarization component, these findings suggest that the electrical stimulation altered the electrode surface rather than the bulk tissue and fluid in the cochlea.